IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMKN 1 RIMBA MELINTANG TAHUN PELAJARAN 2015/2016. - Iis Fitriani; Imam Mahadi; Darmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study is classroom action research (PTK) which aims to improve the biological activity and learning outcomes of students with the implementation of cooperative learning model students teams achievement division (STAD) in class X SMK 1 Rimba Melintang in the academic year 2015/2016. The study was conducted in March-May 2016. The subjects were students of class X SMK 1 Rimba Melintang 2015/2016 school year with the number of 24 people (17 students and 7 students). The study took place during the second cycle in which the first cycle with the materials describe the process of catabolism products (cellular respiration) and the second cycle by the materials describe the process of anabolism product (photosynthesis) conducted three meetings, including daily tests. Parameters measured were the activities and student learning outcomes which consists of the absorption of students and student learning completeness, awards groups, student activities and teacher's activities. When implementing the learning activities consisting of four indicators and activity when carrying out the percentage of groups that are observed by teachers and teacher activity by giving the check mark (√) during activities diobservasikan by the observer. Absorptive capacity of the students in the first cycle of 76.66% (enough) and the second cycle of 85.42% (excellent). Mastery learning in the first cycle were completed and 83.33% increased in the second cycle is 95.83%. Group awards in the first cycle there are two super group and the second cycle there are 3 super groups. Average student activity in cycle I 76.56% (or less) and the second cycle increased to 80.20% (excellent). The average teacher activity increased by 81.81% (excellent) and the second cycle of 95.45% (excellent). From these results it can be concluded that the model type STAD cooperative learning can enhance the biological activity and learning outcomes of students of class X SMK 1 Rimba Melintang in the academic year 2015/2016.Keywords: Student activity, Teacher Activity, Cooperative Model Type STAD.